RANCANG BANGUN SISTEM INFORMASI PENJUALAN KERUPUK KUSARI BERBASIS WEB PT. PUTRA SUGANDA ROHAYATI KARAWANG: Information System Design;Sales System Sistem;Website - Rina Nurmalasari; Mike Amelia; Suryani, Nining (LP2M Universitas Nurdin Hamzah, 2021)
PT. Putra Suganda Rohayati is a micro industrial company in the field of cracker marketing that has long been competing in the market in the industrial world. This company has a data collection system in conventional financial reports so that it often has difficulty checking incoming and outgoing goods reports as well as missing and incomplete administrative data collection, it takes a long time to make reports on proof of purchase transactions, marketing that is still not familiar with online systems. Therefore, in order to improve the company's business transformation to be more effective and competitive, PT. Putra Suganda Rohayati needs information technology, namely web-based sales so that it can collect data that is more systematic, accurate, efficient, to provide easier services to consumers such as ordering goods without the need to come to the factory and online transactions in order to reach a wide market.